2007
DOI: 10.1002/icd.464
|View full text |Cite
|
Sign up to set email alerts
|

Convergence between physiological, facial and verbal self‐report measures of affective empathy in children

Abstract: The present study investigated the degree of convergence between three different measures of vicarious affective responsiveness (affective empathy) - verbal self-report, facial expression and change in heart rate - in typically developing children (N=29, aged 8-10 years), when presented with an emotionally evocative film. Although convergence between physiological and verbal measures was only at chance levels, convergence between facial and physiological measures, and between facial and verbal measures was sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 52 publications
(55 reference statements)
1
25
0
Order By: Relevance
“…The preliminary findings of the present study, if replicated, extend the results of the study by Anastassiou-Hadjicharalambous and Warden [23] for typically-developing children, to CD populations. Taken together, these findings suggest that indirect self-reports do not adequately tap the capacity for vicarious arousal in children, at least in this age range.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The preliminary findings of the present study, if replicated, extend the results of the study by Anastassiou-Hadjicharalambous and Warden [23] for typically-developing children, to CD populations. Taken together, these findings suggest that indirect self-reports do not adequately tap the capacity for vicarious arousal in children, at least in this age range.…”
Section: Discussionsupporting
confidence: 87%
“…The most evocative episode within this sequence of events was identified with the assistance of 15 postgraduate psychology students, and 15 typically developing children (aged 8-10) who unanimously selected the final storm, thunder and broken glass episode, the duration of which was 8 s. These 30 judges were also requested to label Ben's emotional response in this final episode, and they unanimously said that he was scared. This film has been piloted and used in previous investigations of children's vicarious responsiveness, with a similar age group, and has been found to elicit the predicted vicarious affective responses [23].…”
Section: Stimulus Film [55]mentioning
confidence: 99%
See 1 more Smart Citation
“…The limitations associated with particular measures of affective empathy suggest that no single measurement is perfect. Studies examining the convergence between different measures of affective empathy show that some measurements, such as self-report measures and facial responsiveness, correlate with each other (Anastassiou-Hadjicharalambous & Warden, 2007), suggesting there is a common construct that is tapped by each measure. This points to the importance of measuring affective empathy using a multi-method approach to examine whether OXT enhances different components of affective empathy.…”
Section: Oxytocin Empathy and Eye-gaze 17mentioning
confidence: 99%
“…Another study addressing the relationships between measures of affective empathy in children found that although the relationship between self-report and physiological measures was inconclusive, there was a relationship between verbal and facial measures and facial and physiological measures (Anastassiou-Hadjicharalambous & Warden, 2007). The authors noted that the discrepancy in the results could be due to developmental and age issues (i.e., limited emotional vocabulary) in researching children or methodological issues (i.e., measuring HR during the presentation of stimuli and then doing a reflective self-report; AnastassiouHadjicharalambous & Warden).…”
Section: Empathymentioning
confidence: 99%